(untitled) (AYUSHDHARA, 2024)
At the moment, the most prevalent ailment dominating the citizenry is Janu Sandhigata Vata. The term Sandhigata Vata Stated in words like "Sandhi" and "Vata" are used to explain the Sandhigata Vata concept. When the joint, or Sandhi, is embedding by Vata, it manifests as Shotha (swelling), Sandhi shula (pain), and restriction in joint movement. Clinical symptoms of Janu Sandhigata Vata are almost identical to those of the condition known as osteoarthritis in contemporary science. According to Ayurveda, Acharays has also explained in a type of Vatavyadhi as a Janu Sandhigata Vata (knee osteoarthritis) which is dominating role in old age, commonly due to Vata Prakupita and Dahtaukshaya. In the present realm of is difficult task for the therapist cause of their chronicity (according to nature of disease or according to patient ignorance in the initial stage of the disease), uncorrectable in late phase. Today, there are many treatments available in modern medicine, including pain relievers, anti-inflammatory drugs, muscle relaxants, calcium and vitamin D supplements, steroids, and physical therapy. However, these treatments can have limited success and may cause side effects if used for a long time. Ayurveda provides different options for treating Janu Sandhigata Vata, such as Panchakarma, Raktamokshna, Agnikarma, and various Ayurvedic medicines.